2018
DOI: 10.1155/2018/8701851
|View full text |Cite
|
Sign up to set email alerts
|

Plasma YKL-40 Elevation on Admission and Follow-Up Is Associated with Diastolic Dysfunction and Mortality in Patients with Acute Myocardial Infarction

Abstract: Objective The aim of the study was to determine an association between the plasma YKL-40 level and echocardiographic left ventricle systolic and diastolic function parameters in patients with acute myocardial infarction. Subjects and Methods The study included 46 patients with acute myocardial infarction. Serum brain natriuretic protein (BNP) and YKL-40 levels were analyzed on admission and after one month. Left ventricle systolic and diastolic functions and Tei index were computed by transthoracic echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[19][20][21] Currently, YKL-40 is not only associated with pulmonary diseases, but also considered to be an independent biomarker of cardiovascular and cerebrovascular diseases, such as carotid artery atherosclerosis, myocardial infarction, ischemic stroke, spontaneous subarachnoid hemorrhage and intracerebral hemorrhage. [10][11][12]22 Park et al reported that YKL-40 levels might be associated with stroke severity, infarct volume and clinical outcome of 105 Korean AIS patients. 10 However, this is a small-size study without prospective information.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Currently, YKL-40 is not only associated with pulmonary diseases, but also considered to be an independent biomarker of cardiovascular and cerebrovascular diseases, such as carotid artery atherosclerosis, myocardial infarction, ischemic stroke, spontaneous subarachnoid hemorrhage and intracerebral hemorrhage. [10][11][12]22 Park et al reported that YKL-40 levels might be associated with stroke severity, infarct volume and clinical outcome of 105 Korean AIS patients. 10 However, this is a small-size study without prospective information.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, serum NE was significantly reduced after LAD ligation surgery, whereas Schisandra could significantly reduce serum NE in a dose-dependent way, indicating that Schisandra could inhibit the sympathetic nervous system ( Figure 9B ). Additionally, the serum NT-BNP was significantly reduced after treatment with Schisandra ( Figure 9C ), which suggests that left ventricular wall tension and blood pressure can be significantly reduced ( Demirtas et al, 2018 ; Pala et al, 2018 ; Shen et al, 2018 ; Xiong et al, 2018 ). These results indicate that Schisandra could significantly inhibit the activation of the sympathetic nervous system so that the contractility of the left ventricle could also be reduced.…”
Section: Resultsmentioning
confidence: 92%
“…Studies have shown that serum YKL-40 is elevated in patients with acute myocardial infarction and chronic coronary heart disease (11,32). The results of previous studies showed (33) serum YKL-40 had prognostic significance in AMI patients, plasma YKL-40 was significantly increased in AMI patients and remained higher than that in healthy subjects after 1 month, and was associated with elevated serum BNP, diastolic dysfunction, and long-term increased overall mortality. Yang et al ( 14) further investigated patients with acute STEMI who underwent primary percutaneous coronary intervention (PCI) and were followed for 24 months.…”
Section: Discussionmentioning
confidence: 98%